A case study: Comparing testers for means and variances in a balanced incomplete block design. Issue Volume 33:Issues 3(2021) (3rd July 2021) - Hamada, M. S.; Yeamans, K. A.; Harris, C. P.
Abstract: In this article, we present a gauge R & R study that is different from the standard setup in several ways. A balanced incomplete block design (BIBD) was used to collect the data because the measurement is destructive. Besides addressing reproducibility, differences in repeatability (i.e., tester variances) were also of interest. Here we use Bayesian methods to analyze the study data to address whether the three tester means and variances are similar. We also consider what happens if the BIBD structure of the data and possibly different tester variances are ignored in analyzing the study data.